Importance-Performance Analysis (IPA) approach of marine park tourism destinations: a case study of Kapas Island Marine Park, Terengganu - Mohd Adam, Syamimi; Mohammad Afandi, Syamsul Herman; W. Mohamad, Wan Norhidayah; Ahmad Shuib; Awang, Raudhatul Jannah (Universiti Putra Malaysia Press, 2024)
Tourism in the marine park is vital to tourist satisfaction. Tourism and sustainability must be balanced in sensitive regions like marine parks. Tourist feedback helps balance and sustain marine park management. Kapas Island Marine Park (KIMP) in Terengganu receives a high number of tourists annually. The resources and the tourist experience may be adversely affected by excessive utilisation of marine resources. It may have long-term effects on the travel industry. This research has adopted an Importance-Performance Analysis (IPA) to scrutinise how visitors view the execution of 23 attributes of KIMP. The objective of this study is to show that various tourism attributes affect tourist satisfaction, as well as to discover the satisfaction- and dissatisfaction-generating attributes that may be found in the marine tourism experience. In addition, this research discusses how IPA may be used to influence future visitor research and management at marine park sites. The findings of this research were obtained by a questionnaire survey of 310 visitors to the KIMP during May and June 2022. The results are displayed on a grid with four quadrants; facilities are available to ensure the safety and security of the visitors (Quadrant One); attributes are already providing good service, and therefore, performance must be sustained (Quadrant Two); the fundamental amenities or necessities as seen by visitors (Quadrant Three); attributes that have a low significance score but obtained a high-performance score (Quadrant Four). These findings potentially provide a reference for thorough development strategies for a marine park tourism destination.